Pengaruh Luas Ungkapan Sukarela dalam Laporan Tahunan terhadap Earnings Response Coefficient (ERC) - Widiastuti, Harjanti (Journal of Accounting and Investment, 2004)
This study examines whether voluntary corporate disclosure level published in annual report affects the relation between current stock return and contemporaneous annual earnings. The purpose of the study is to investigate whether the variances in corporate disclosure level published in annual report of companies listed on the Jakarta Stock Exchange (the JSX) affects the value-relevance of earnings information proxied by earnings response coefficient (the ERC). This study is preliminary attempt to combine two research issues: the informativeness of earnings (ERC) and the informativeness of disclosures, which have been separately investigated by previous studies. The findings are expected to give preliminary evidence about cross-sectional differences in current ERC associated with voluntary corporate disclosure level published in annual report. It is hypothesized that voluntary corporate disclosure level published in annual report has a negative effect on the ERC. To test the hypothesis, current stock returns are regressed against current earnings changes. The sample consists of 67 of annual reports of companies listed on the JSX as of December 31, 1995. The study finds evidence that voluntary corporate disclosure level published in annual report have a statistically positive effect on the ERC at 0.10 significant levels. This result remains consistent after controlling for other factors that have been shown to influence the earnings response coefficient. The result does not support the hypothesis that voluntary corporate disclosure level published in annual report has a negative effect on the ERC. The possible reason is that disclosures in annual report insufficiently reveal the information about companies’ future prospect. However, the result of sensitivity analysis using fundamental return model shows that voluntary corporate disclosure level published in annual report has a negative effect on the ERC, but not statistically significant.